Improving the Quality of Environmentally Friendly Liquid Smoke Distillation Process to Increase Artisan Income - Sukamta, Sukamta; Sudarja; Marlina, Rini; Muzthohidun, Muhammad; Winarno, Agus (Universitas Muhammadiyah Surakarta, 2023)
The problems the Smoke-liquid Craftsman Group often faces are production capacity, product quality, and low selling prices. Low production capacity due to the limited ability distillation machine. The low quality of smoke-liquid products is due to the absence of standard quality. The smoke produced from the coconut shell charcoal production process has the potential to disturb the environment, so it has been carried out the process of melting smoke into liquid, which is then called smoke-liquid. However, the resulting smoke-liquid is still mixed with ash, brown colour, and intense aroma, and still contains much tar, so it does not meet the standard quality for food preservatives the price is low. The objective of this activity is to apply appropriate technology is carried out by enforcing standard product quality and repairing distillation machines to produce high-quality smoke liquid. This one is to support renewable and environmentally friendly energy programs while being able to increase revenue. Appropriate Technology (TTG) is in the form of improvements in distillation technology, which was previously a distiller using annular pipes, where the inner pipe is 1/2 inch. The outer pipe diameter is 1.5 inches and is changed with parallel heat pipe exchanger technology using an inner pipe with a diameter of 1 inch and an outer pipe with a diameter of 4 inches. The result of this service is prototyping a new distillation machine that can increase the production capacity and quality of liquid smoke that meets the specified standard quality and increase the selling price four times.